Mathematical analysis of trend indicators of Internet security resources cyber-diagrams dynamics in the Republic of Kazakhstan - Shayakhmetova, B.K.; Omarova, Sh.E.; Drozd, V.G. (Bulletin of the Karaganda University. Mathematics Series, 2019)
In the research the development of a mathematical model for predicting threats of information security of Internet resources is carried out, which allows, based on the minimum amount of input data, to indicate the dynamics of the development of possible threats in the life cycle of information systems, which may in the long run be a reason for shaping the costs of preventing threats to information security.